The Power of Thriving: How Social Sustainability in Organizations Relies on a Culture of Knowledge Sharing - Zeynep Gormezoglu; Safiye Sahin; Kerem Toker (SAGE Open, 2024)
At the beginning of the third millennium, United Nations Sustainable Development Goals and the United Nations Millennium Development Goals opened a discussion on the role of human beings in the future. Concerns about social welfare created legal and normative pressures on organizations on social sustainability. To understand the social sustainability in organizations, we developed a research model based on the socially embedded model. From this perspective, this study aims to examine the relationship between knowledge sharing and social sustainability and determine the mediating role of thriving in this relationship. In this framework, we analyzed the data collected from 418 people working in the technology sector. The results have shown that thriving has a significant mediating role in the effect of explicit and implicit knowledge sharing on social sustainability ( p  < .01). As a result, the organizations encouraging knowledge sharing leads to high thriving levels in their employees, which in turn leads to the implementation of more social sustainability practices within their organizations. This study contributes both theoretically and practically by demonstrating that organizations fostering knowledge sharing lead to higher levels of employee thriving, subsequently facilitating the implementation of social sustainability practices, thus advancing understanding and guiding actions toward sustainable organizational development.